Flexural behavior of geopolymer-concrete beams longitudinally reinforced with GFRP and steel hybrid reinforcements. (1st March 2019) - Maranan, G.B.; Manalo, A.C.; Benmokrane, B.; Karunasena, W.; Mendis, P.; Nguyen, T.Q.
Highlights: Geopolymer-concrete beams longitudinally reinforced with GFRP and steel bars. Behaviour of beams with different GFRP-to-steel reinforcement ratios. Evaluation of the failure mode, load–deflection behavior and ductility. Prediction of the load capacity and comparison with available design standards. Abstract: This paper presents the flexural behavior of geopolymer-concrete beams longitudinally reinforced with a hybrid of glass-fiber-reinforced-polymer (GFRP) and steel bars. Seven geopolymer-concrete beams with different ratios and configurations of GFRP-to-steel reinforcement were designed, cast, and tested up to failure using the four-point static bending test. Based on the experimental results, the hybrid beams showed better serviceability and ductility and up to 15% higher strength than their counterpart geopolymer-concrete beams reinforced solely with GFRP bars. Increasing the reinforcement ratio increased overall beam performance. The hybrid beams reinforced with steel bars at the top and with GFRP bars at the bottom produced higher stiffness and strength at concrete crushing than their counterpart beams with hybrid tensile reinforcement. The tested geopolymer-concrete hybrid beams yielded better bending-moment capacities than the normal-concrete hybrid beams. Both ACI 440.1R-15 and CSA S806-12 conservatively predicted the flexural strength and mid-span deflection at service load of the hybrid beams.